(untitled) (CIPEEX, 2022)
IT IS ESTIMATED THAT BETWEEN 10 TO 20% OF WOMEN WILL HAVE A URINARY TRACT INFECTION AT SOME POINT. THE ANATOMICAL AND PHYSIOLOGICAL TRANSFORMATIONS THAT OCCUR IN THE URINARY TRACT IN THIS FAVOR THE DEVELOPMENT OF SYMPTOMATIC URINARY INFECTIONS. REDUCTION OF RENAL CAPACITY TO CONCENTRATE URINE DURING PREGNANCY IS KNOWN TO REDUCE THE ANTIBACTERIAL ACTIVITY OF THIS FLUID, EXCRETING SMALLER AMOUNTS OF POTASSIUM AND HIGHER AMOUNTS OF GLUCOSE AND AMINO ACIDS, AND HORMONAL DEGRADATION PRODUCTS, PROVIDING A SUITABLE MEANS FOR PROLIFERATION BACTERIAL. IN THIS PERIOD, IT IS ALSO OBSERVED THAT THE URINE OF THE PREGNANT WOMAN PRESENTS A MORE ALKALINE PH, FAVORABLE SITUATION TO THE GROWTH OF THE BACTERIA PRESENT IN THE URINARY TRACT. QUALITATIVE URINE TESTING IS IMPORTANT TO DETECT BACTERIURIA AND PYURIA THAT ARE INDICATORS OF URINARY TRACT INFECTION (UTI). THE ASSOCIATION BETWEEN URINARY TRACT INFECTION AND WORSENING OF GESTATIONAL PROGNOSIS IS ALREADY KNOWN. AMONG THE COMPLICATIONS ARE LABOR AND PRETERM DELIVERY, PREMATURE RUPTURE OF AMNIOTIC MEMBRANES, RESTRICTION OF INTRAUTERINE GROWTH, LOW BIRTH WEIGHT AND PERINATAL DEATH. THE OBJECTIVE WAS TO ESTIMATE THE PREVALENCE OF BACTERIURIA IN PREGNANT PATIENTS FROM URINE SAMPLES ANALYZED IN THE LABORATORY OF CLINICAL ANALYZES OF UNIEVANGELICA. THE PRESENT STUDY WAS A PROSPECTIVE, CROSS-SECTIONAL STUDY CONDUCTED AT THE LABORATORY OF CLINICAL ANALYZES OF UNIEVANGLICA LOCATED IN ANÁPOLIS - GOIS, BRAZIL, WHERE THE CHEMICAL, PHYSICAL AND SEDIMENTOLOGICAL CHARACTERISTICS OF URINE WERE EVALUATED. THE METHODOLOGY WAS BASED ON A SEDIMENTOSCOPIC EVALUATION OF THE SAMPLES COLLECTED IN THE YEAR 2017 IN PREGNANT WOMEN. THE PRESENCE OF BACTERIA IN URINARY SEDIMENT ANALYSIS AS WELL AS QUANTIFICATION WERE CONSIDERED FOR THE DIAGNOSIS OF BACTERIURIA. THE WORK WAS APPROVED BY THE RESEARCH ETHICS COMMITTEE OF THE UNIEVANGELICA INSTITUTION UNDER PROTOCOL NUMBER: 2,147,426 / 2017. OF THE 1000 SAMPLES PERFORMED IN 2017, 73 WERE OF PREGNANT WOMEN REPRESENTING A GENERAL PREVALENCE OF 7.3%. THE PRESENCE OF BACTERIA WAS OBSERVED IN 38 (52.0%) PATIENTS, WITH 10 (7.3%) SHOWING INCREASED BACTERIA, WHICH IS OF GREATER CLINICAL RELEVANCE FOR DIAGNOSIS AND TREATMENT, AND 28 (20.44%) HAD MILD BACTERIA THIS DIAGNOSIS IS INCONCLUSIVE, SUGGESTING THE BEGINNING OF INFECTION OR CONTAMINATION OF THE SAMPLE. ONLY 6 (4.38%) OF THE SAMPLES DID NOT PRESENT BACTERIA IN THE URINE AND29 (21.17%) PRESENTED RARE BACTERIA AND COULD BE INDICATIVE OF SAMPLE CONTAMINATION. 28 (20.44%). THE ITU REPRESENTS A RELEVANT SOURCE OF MATERNAL AND PERINATAL COMPLICATIONS, IT IS INDISPUTABLE TO IDENTIFY AND TREAT THIS FORM OF INFECTION DURING PRENATAL CARE, AVOIDING COMPLICATIONS, AND TREATMENT IS MADE POSSIBLE BY THE ANTIBIOGRAM. THE TREATMENT CONTROL IS DONE USING THE UROCULTURE, REQUESTED SEVEN DAYS AFTER THE END OF THE TREATMENT, MONTHLY IN THE FIRST THREE MONTHS AND, IF ALL ARE NEGATIVE, BIMONTHLY THEREAFTER UNTIL THE END OF THE PREGNANCY. PREVENTION AND EARLY DIAGNOSIS PROVIDE SAFEGUARDS FOR THE PREGNANT WOMAN AND THE FETUS, SINCE THEY ALLOW SAFE AND IMMEDIATE CLINICAL INTERVENTIONS. IT IS CONCLUDED FROM THE PRESENT STUDY THAT THE RESULTS FOUND CONFIRM THE PREVALENCE OF BACTERIURIA IN PATIENTS IN THE GESTATIONAL PERIOD. KNOWING THAT THIS IS AN ALARMING STATE, RAPID, OBJECTIVE AND INDIVIDUALIZED TREATMENT SHOULD BE A PRIORITY IN THE THERAPEUTIC MANAGEMENT OF THESE PATIENTS.